Impact of different growing media on propagation of bougainvillea (Bougainvillea spp.) through hardwood stem cuttings in Chitwan, Nepal - Panthi, Swikriti; Pant, Mukesh; Chand, Roshan; Devkota, Toran (International Journal of Horticultural Science, 2025)
An experiment was conducted in Rampur, Chitwan, Nepal, in a Randomized Complete Block Design (RCBD) with five treatments: T1 (sand:soil, 1:1) [control], T2 (sand:cocopeat:perlite, 1:1:1), T3 (perlite:sand, 1:1), T4 (sand:cocopeat, 1:1), and T5 (peat moss:perlite, 1:1). Each treatment was replicated four times with a total of 300 planted cuttings. The key parameters evaluated were sprouting percentage, shoot growth (length, leaf number, and branch number), and root development (length, number, fresh, and dry biomass). Analysis of data was done using R-Studio, and Duncan’s Multiple Range Test (DMRT) was performed at a 5% significance level. The results revealed that peat moss:perlite (1:1) demonstrated the highest shoot growth with shoot length of 6.00, 14.38 and 28.78 cm at 30, 60, and 90 Days After Planting (DAP) respectively. Leaf number were 6.25, 13.12, and 19.57, while branch numbers were 1.76, 2.00, and 2.18 at the same intervals., Additionally, the fresh root weight was recorded 8.74 g. Sand:cocopeat:perlite (1:1:1) recorded the highest sprouting percentage (81.66%) and root length (17.11 cm), while sand:cocopeat (1:1) achieved the highest root number (18.37) and dry root weight (0.99 g). Perlite:sand (1:1) exhibited moderate performance with sprouting percentage 69.99%, and root length 12.56 cm. In contrast, control (sand:soil) showed the least favorable results with the lowest sprouting percentage (58.33%), the fewest number of roots (7.81), and the minimum root length (9.73). This study concludes that peat moss:perlite (1:1) is the most effective growing medium for bougainvillea propagation, offering a practical solution to enhance rooting success and growth performance. Sand:cocopeat (1:1) with maximum dry weight of root and maximum number of roots emerged as a reliable alternative, proving the effectiveness of the medium.